EXPERIMENT AND SIMULATION RESEARCH ON UNIFORM SUPERCHARGED FATIGUE CRACK INITIATION OF AIRCRAFT FUSELAGE SKIN - LIU LiPing; ZHANG Fang; ZHONG XiaoKun; BAO Rui; XU JianXin; QIN WenChao (Jixie qiangdu)
The fatigue crack initiation of the fuselage structure skin under the uniform supercharged cyclic load of 0 ～ 7. 8 Psi was experimentally studied by the self-made aircraft fuselage skin uniform supercharged fatigue simulation device. The location of the fatigue crack initiation of the fuselage structure skin and the sequence of fatigue crack initiation are studied by finite element analysis. The research showed that under the uniform supercharged fatigue load,fatigue crack initiation occurred on the left and right sides of the nail holes. The fatigue crack initiation sequence is mainly related to the maximum Von-Mises stress value at the initiation site,but also related to the tightness of the connection between the skin and the stringer.